Screening Oropharyngeal Dysphagia in Older Adults A Risk Factor for in-Hospital Mortality With COVID-19 Infection? - ŞENTÜRK DURMUŞ, NURDAN; TUFAN ÇİNÇİN, ASLI (My University, 2024)
This study investigated the use of the Eating Assessment Tool 10 (EAT-10) in predicting clinical outcomes in older adults hospitalized with COVID-19 infections between February and June 2021. The EAT-10 was performed for all patients. Thirty one percent and 23% of the 153 patients had oropharyngeal dysphagia risk and in-hospital mortality, respectively. Older age (hazard ratio: 1.08; 95% confidence interval, 1.03-1.13; P = .003) and higher EAT-10 score (hazard ratio: 1.02; 95% confidence interval, 1.01-1.04; P = .043) were associated with in-hospital mortality. Older age and having increased risk of oropharyngeal dysphagia were independently associated with a higher risk of in-hospital mortality in older patients with COVID-19. Key words: COVID-19, dysphagia, EAT-10, in-hospital mortality, older adults
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE; COVID-19; dysphagia; EAT-10; in-hospital mortality; older adults